Oral etoposide in heavily pre-treated metastatic breast cancer: A retrospective series. (April 2018) - Giannone, G.; Milani, A.; Ghisoni, E.; Genta, S.; Mittica, G.; Montemurro, F.; Valabrega, G.
Abstract: Background: Patients with metastatic breast cancer (MBC) can derive clinical benefit from several subsequent lines of chemotherapy. However, in heavily pre-treated patients, agents with clinical activity, a favourable side effects profile and a convenient administration modality are preferred. Patients and Methods: We retrospectively analyzed 110 patients with previously treated MBC, who received oral etoposide at the dose of 50 mg/day for 20 days in 28 days cycles, between 2003 and 2017. Because this was not a prospectively planned study, to describe the clinical performance of oral etoposide we adopted the approach suggested by Dzimitrowicz and colleagues ( J Clin Oncol . 2016; 34:3511–17); Tumour Response (TR) was defined as the proportion of physician-reported clinical or imaging response; Prolonged Duration on Therapy (PDT) as the proportion of non-progressing patients whose treatment lasted more than 6 months. Furthermore, we evaluated median duration on therapy (TD) and median Overall Survival (OS) by the Kaplan Meier method. Results: The median number of previous chemotherapy lines was 5 (range 2–8). TR, PDT, median TD and median OS were 6.4%, 18.2% 4 (range 3.5–4.5) and 10.6 (range 8.4–12.8) months respectively. Interestingly, etoposide activity was unrelated to the number of previous lines and type of metastatic involvement. Oral etoposide was well tolerated with only two patients discontinuing therapy due to toxicity. Conclusions: In this large, single Institution, real practice analysis oral etoposide is a valuable and safe option for pre-treated metastatic breast cancer patients and might be considered in patients failing other approaches, but still suitable for chemotherapy. Highlights: Oral etoposide is a well-tolerated agent used in treatment of several types of neoplasms. We retrospectively evaluated 110 pre-treated metastatic breast cancer patients receiving oraletoposide at our institution. Oral etoposide was active and well tolerated in patients failing a median of 5 prior chemotherapy lines. This real world study suggests that oral etoposide is a therapeutic option in pre-treated metastatic breast cancer patients.